Public perceptions of responsibility for recommended food policies in seven countries. (10th February 2023) - Pinho-Gomes, Ana-Catarina; Booth, Leon; Pettigrew, Simone
Abstract: Background: Food policy is important to promote healthy and sustainable diets. However, who is responsible for developing and implementing food policy remains contentious. Therefore, this study aimed to investigate how the public attributes responsibility for food policy to governments, individuals and the private sector. Methods: A total of 7559 respondents from seven countries [Australia ( n  = 1033), Canada ( n  = 1079), China ( n  = 1099), India ( n  = 1086), New Zealand ( n  = 1090), the UK ( n  = 1079) and the USA ( n  = 1093)] completed an online survey assessing perceived responsibility for 11 recommended food policies. Results: Overall, preferred responsibility for the assessed food policies was primarily attributed to governments (62%), followed by the private sector (49%) and individuals (31%). Respondents from New Zealand expressed the highest support for government responsibility (70%) and those from the USA the lowest (50%). Respondents from the USA and India were most likely to nominate individuals as responsible (both 37%), while those from China were least likely (23%). The private sector had the highest attributed responsibility in New Zealand (55%) and the lowest in China and the USA (both 47%). Support for government responsibility declined with age and was higher among those on higher incomes, with a university degree, and who perceived themselves to consume a healthy diet or be in poor health. Conclusions: Across seven diverse countries, results indicate the public considers government should take primary responsibility for the assessed food policies, with modest contribution from the private sector and minority support for individual responsibility.